2003
DOI: 10.1038/sj.bjc.6600801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epoetin β on quality of life in patients with malignant disease

Abstract: This open-label, prospective study was conducted to compare the impact of epoetin b vs standard care on quality of life (QoL) in anaemic patients with lymphoid or solid tumour malignancies. A total of 262 anaemic patients (haemoglobin [Hb]p11 g dl À1 ) were randomised to a 12-week treatment with s.c. epoetin b (initial dose 150 IU kg À1 three times weekly) or standard care. Transfusions were recommended for both groups at an Hb threshold of 8.5 g dl À1 . The primary efficacy variables were improvement in QoL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
1
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 30 publications
1
114
1
5
Order By: Relevance
“…The pooled risk of these outcomes did not differ significantly between groups (RR for cardiovascular events 1.12, 95% CI 0.83 to 1.50, I 2 = 0%; RR for hypertension 1.41, 95% CI 0.94 to 2.12, I 2 = 0%). Health-related quality of life One otherwise eligible trial reported changes in generic measures of overall quality of life; 37 however, we excluded it because it was the only study that reported these outcomes.…”
Section: Cardiovascular Events and Hypertensionmentioning
confidence: 99%
“…The pooled risk of these outcomes did not differ significantly between groups (RR for cardiovascular events 1.12, 95% CI 0.83 to 1.50, I 2 = 0%; RR for hypertension 1.41, 95% CI 0.94 to 2.12, I 2 = 0%). Health-related quality of life One otherwise eligible trial reported changes in generic measures of overall quality of life; 37 however, we excluded it because it was the only study that reported these outcomes.…”
Section: Cardiovascular Events and Hypertensionmentioning
confidence: 99%
“…Erythropoietic agents have been shown to increase haemoglobin (Hb) levels and reduce transfusion requirements in patients with cancer (Littlewood et al, 2001;Ö sterborg et al, 2002;Vansteenkiste et al, 2002;Boogaerts et al, 2003;Bohlius et al, 2004). Treatment with epoetin also alleviates fatigue and other symptoms of anaemia and produces significant improvements in QoL compared with placebo or standard transfusion therapy (Ö sterborg et al, 2002;Boogaerts et al, 2003).…”
mentioning
confidence: 99%
“…A meta-analysis of data from 15 randomized controlled trials of epoetin showed a consistently high rate of hematologic response, with an overall risk ratio of 3.42 (95% confidence interval [CI], 3.03-3.06) relative to control (Table 1) [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The likelihood of Hb response is at least as large when the starting Hb level is 10-12 g/dl as it is when baseline Hb is <10 g/dl.…”
Section: Esasmentioning
confidence: 99%